The role of emotional styles in information avoidance regarding negative news - Torabi, Mahsa; Khezri, Hiwa; Torabi, Samaneh (Information Research an international electronic journal, 2025)
Introduction. This study explores the influence of emotional styles on students’ information avoidance behaviour, particularly about negative news. Method. Using a sample of participants, we employed the Emotional Styles Questionnaire (ESQ) to measure emotional styles, alongside an information avoidance questionnaire to assess participants’ tendencies to avoid distressing news. Cronbach’s Alpha for both questionnaires indicated good reliability. Analysis. Data analysis involved confirmatory factor analysis (CFA) and regression analysis to validate the instruments and explore the relationships between emotional styles and information avoidance. Results. Results demonstrated that higher resilience and greater sensitivity to context are significantly associated with increased information avoidance among students. Conclusion. These findings suggest that students with resilience and sensitivity to context emotional styles engage in strategic information avoidance to manage their emotional well-being. The study’s implications highlight the need for tailored interventions to enhance emotional resilience and adaptive coping strategies, offering insights for mental health professionals, educators, and policymakers. Future research should investigate cultural differences and longitudinal changes to further understand the dynamics of information avoidance. This research underscores the importance of considering emotional dispositions in information-seeking behaviours, contributing to the broader theoretical framework of emotional regulation.